La ville du Sud en temps réel - Benjamin Bosselut; Marion Broquère; Armelle Choplin; Simon Nancy (EchoGéo)
This paper shows how the kite aerial photography can be used in urban studies, relying on a concrete application experience for a social housing program in Nouakchott (Mauritania). Particularly, it is useful in order to study Southern cities involved by urban sprawl. This tool allows to see urban developments « in real-time » and should compensate the lack of mapping up-to-date data. This article explains how we can use kite pictures and technical procedures to produce exploitable data.